國際華語教材跨文化詞彙分析： 以《中學生探世界》為例 The Intercultural Vocabulary and Awareness of an International Chinese Teaching Material: A Case Study - 蔡雅薰 Ya-Hsun Tsai; 張孟義 Meng-I Chang; 余信賢 Xin-Xian Yu (Higher Education Foundation, 2022)
華語文教學的跨文化理解，不能脫離全球背景的教學核心。國際華語教學內容應具備全球視角的多元選材，培養學生從語文教學的過程中建構跨文化意識。本研究聚焦於《中學生探世界》的跨文化詞彙，透過語料庫分級，探究跨文化詞彙及詞表類別的基礎建構。本研究採用定量與定性分析法，分別透過國立臺灣師範大學的閱讀詞彙計量系統及國家教育研究院的語料庫，分析教材中跨文化詞彙的難易度。 其次，重新檢視跨文化詞彙分級的必要性。研究結果顯示，此教材跨文化詞彙共計714項，其中646項被判定為超綱詞，其比率達90.48%。同時，更有79.55%的詞彙並無分級。詞彙分級和詞表雖能規範常用詞語的頻率，卻隱藏了跨文化詞彙在全球情境及國際教育中的重要性。 The intercultural understanding of Chinese language teaching cannot be separated from the core of education involving global context. In the international Chinese language teaching, the teaching content should have a diverse selection of materials from a global perspective, cultivate students to construct intercultural awareness in the process of language learning, and increase the sensitivity to compare cultural differences, in order to promote the mutual understanding between cultures. This research focuses on the intercultural vocabulary in a textbook Exploring the World for Middle School Students. This study conducts both quantitative and qualitative analyzes to explore the classification of intercultural vocabulary through two different corpuses. One of which is the reading vocabulary measurement system developed by the National Taiwan Normal University, and the other one is the corpus developed by the National Academy of Education. First, the difficulty of intercultural vocabulary in the textbook is analyzed. Second, the necessity for intercultural vocabulary would also be re-examined from the global viewpoint. The results show that in the textbook, there are 714 intercultural words, of which 646 are judged as level-exceeded words, with the ratio of 90.48%. At the same time, 79.55% of the intercultural words are not included in the ranking and classification in the vocabulary list of these corpuses. Even though these corpuses are useful to point out the frequency of common vocabulary, it hides the phenomenon that many intercultural words are excluded from the list of common-used vocabulary. More significantly, it is underestimated to realize the importance of the intercultural vocabulary in the international involvement of global issues.